Accelerated Iron Oxide Nanoparticle Degradation Mediated by Polyester Encapsulation within Cellular Spheroids. (18th September 2013) - Mattix, Brandon; Olsen, Timothy R.; Moore, Thomas; Casco, Megan; Simionescu, Dan; Visconti, Richard P.; Alexis, Frank
<x xml:space="preserve">Abstract</x> Nanomaterials including gold nanoparticles, polymeric nanoparticles, and magnetic iron oxide nanoparticles are utilized in tissue engineering for imaging, drug delivery, and maturation. Prolonged presence of these nanomaterials within biological systems remains a concern due to potential adverse affects on cell viability and phenotype. Accelerating nanomaterial degradation within biological systems is expected to reduce the potential adverse effects in the tissue. Similar to biodegradable polymeric scaffolds, the ideal nanomaterial remains stable for sufficient time to accomplish its desired task, and then rapidly degrades once that task is completed. Here, surface modifications are reported to accelerate iron oxide MNP degradation mediated by polymer encapsulation, in which iodegradable coatings composed of FDA approved polymers with different degradation rates are used: poly(lactide) (PLA) or copolymer poly(lactide‐co‐glycolide) (PLGA). Results demonstrate that degradation of MNPs can be controlled by varying the content and composition of the polymeric nanoparticles used for MNP encapsulation (PolyMNPs). Incorporated into cellular spheroids, PolyMNPs maintain a high viability compared to non‐coated MNPs, and are also useful in magnetically patterning cellular spheroids into fused tissues for tissue engineering applications. Accelerated degradation compared to non‐coated MNPs makes PolyMNPs a viable alternative for removing nanomaterials from tissues after accomplishing their desired role.